All in how obsessive leaders achieve the extraordinary - Shaw, Robert B. (New York HarperCollins, 2020)
As a psychologist once noted, 'When people with creative energy succeed in putting their obsessional personality traits to good use, everyone benefits.' What personality trait is found in all extraordinary leaders? A passionate commitment to achieving their vision that borders, and sometimes crosses the line into, obsession. Shows leaders and aspiring leaders how obsession, if properly focused and managed, is necessary and productive. Advances in any field almost always depend on a small group of individuals who are completely consumed by the goal they're pursuing. It explores the four types of productive obsession underlying the success of great leaders and their companies: Delighting customers, Creating extraordinary products, Building an enduring company, and Contributing to society.
Includes bibliographical references and index.
Keywords: Leadership